Peningkatan Kemampuan Bahasa Ekspresif Anak Melalui Metode Bercerita dengan Media Audio Visual pada Anak Kelompok B.1 di TK Bakti Pertiwi Kecamatan Baras Kabupaten Pasangkayu - Amal, Azizah; Akbar, Amal; Safitri, Nuraryska (ARZUSIN, 2024)
The main problem in this research is whether using the storytelling method through audio-visual media can improve the expressive language skills of group B.1 children at TK Bakti Pertiwi Kab. Pasangkayu. The aim of this research is to improve children's expressive language skills through storytelling using audio-visual media for Group B.1 children at Bakti Pertiwi Kindergarten, Baras District, Kab. Pasangkayu. The benefits of this research can increase knowledge, especially in improving expressive language skills and it is hoped that it will be beneficial for children, teachers and schools. This type of research is class action research (Class Action Research) which consists of two cycles carried out in 3 meetings each cycle, research procedures include planning, implementation, observation and reflection. The subjects in this research were students of group B.1 TK Bakti Pertiwi Kab.Pasangkayu as many as 16 children. The results of this study showed that in the first cycle after being given action at meetings I, II, and III, there was an increase in children in the Starting to Develop (MB) criteria with a percentage of 43.74%, and in the second cycle after being given action at meetings I, II , and III, there is an increase in children with the criteria of Developing According to Expectations (BSH) with a percentage of 70.13%, which means that they have reached the target of children's development achievements with the criteria of Already Developing According to Expectations (BSH). Based on the research results, it can be concluded that applying the storytelling method through audio-visual media can improve expressive language skills in Group B.1 children at Bakti Pertiwi Kindergarten, Baras District, Kab. Pasangkayu with an average gain of 70.13% with the criteria of Developing According to Expectations (BSH).